Performance analysis of shell and tube type heat exchangers based on computational fluid dynamics (Case Study of Heat Exchangers at PT. XYZ) - Zulfakri, Zulfakri; Lubis, Hasrin; Syukran, Syukran; Azwinur, Azwinur (Journal of Mechafa Engineering and Fabrication, 2025)
Shell and tube heat exchangers are essential components in the process industry, utilizing heat from exhaust gases to superheat steam in the production process. Their performance significantly determines the overall energy efficiency of the system. This study presents a case-based novelty by evaluating the actual performance of a shell and tube heat exchanger at PT. XYZ through Computational Fluid Dynamics (CFD) using Ansys Fluent 17.2. Simulations were conducted to analyze the distribution of temperature, pressure, and fluid velocity, as well as to calculate their effectiveness and LMTD. The simulation results show that the temperature of the cold fluid increases from 11.95°C to 19.35°C, while the temperature of the hot fluid decreases from 62.05°C to 49.55°C. The fluid pressure also decreases significantly, from 1717 Pa to -76.48 Pa on the tube side. The LMTD value is 40.09°C, and the heat transfer effectiveness is 24.95%. To ensure reliability, the simulation results were validated against actual operating data from PT. XYZ. This study contributes by providing a representative picture of the real operating performance of shell and tube heat exchangers, which can serve as a practical basis for improving system design and energy efficiency in the process industry.